The reciprocity in dynamic employment relationships - Matthias Fahn (Johannes Kepler University of Linz, Department of Economics, 2020)
This paper analyzes a dynamic relational contract for employees with reciprocal preferences. I develop a tractable model to investigate how "direct" performance-pay (promising a bonus in exchange for effort) and generous upfront wages (which activate the norm of reciprocity) interact over the course of an employee's career. I show that firms can benefit from committing to paying non-discretionary wages in the future as this boosts their credibibility in the relational contract. The reason is that these wages have to be paid under any circumstances, whereas employees only reciprocate if the firm has kept its promises. Moreover, I demonstrate that more intense competition for workers can intensify the use of reciprocity-based incentives.
Keywords: C73; D21; D86; D90; D91; 330; reciprocity; relational contracts; commitment; norms and social preferences